Why reducing the cosmic sound horizon alone can not fully resolve the Hubble tension - Karsten Jedamzik; Levon Pogosian; Gong-Bo Zhao (Communications Physics, 2021)
It is generally accepted that the Universe is dominated by dark energy but the different methods to measure the Hubble constant disagree, giving origin to what is known as the "Hubble tension”. The authors demonstrate that the sole reduction of the sound horizon is not sufficient to fully resolve the Hubble tension.